Speech act among generation Y students at Universiti Putra Malaysia - Kamarudin, Muhammad Amirul; Hamzah, Zaitul Azma Zainon; Yaakob, Nor Azuwan (Human Resource Management Academic Research Societ, 2021)
Speech acts can be categorized as a forms of utterance which is have aspects of actions that have been produced by a language speaker. Typically, speech act exists in a communication situation that involves a conversation between two parties, that are the speaker and the listener. It can be said that every conversation that has been produced by a language speaker involves an aspect of speech act. Therefore, the conversational analysis has been chosen as the focus of the study to analyze aspects of speech act used by language speakers. Accordingly, this study was conducted to identify the aspects of speech act involved in the conversation of Generation Y students and analyze the use of aspects of speech act based on selected theories. In this study, the researcher has used the research method by making observations and voice recordings involving the conversations of Generation Y students at Universiti Putra Malaysia (UPM). Furthermore, the selection of the sample study was done by using purposive sampling method and this study involved eight recordings of conversations. Each recording of the conversation was transcribed and each data of the study was analyzed qualitatively using the Speech Act Bach and Harnish Theory (1979). The categorization of Speech Act by Bach and Harnish (1979) consists of four act namely constatives, directives, commisives and acknowledgements speech act. However, in this study, the researcher only focused on the constative speech act only. The results of the study showed that each conversation data that was analyzed based on the eight recordings of the conversation involved aspects of the constative speech act. Therefore, this study shows that Generation Y students also used the aspects of speech act in their daily conversations. Each speech act used by the Generation Y students has a specific function or purpose.